Innovative Work Shift for Health Workers in the Health Service Providers in Handling COVID-19 Cases - Iswanto, Acim Heri (UI Scholars Hub, 2020)
Working on shifts has the risk of being exposed to health problems, such as obesity and susceptibility to infections and hypertension. However, shift work is unavoidable for workers in sectors that require non-stop operations, such as health workers in the Health Service Providers. This article presented opinion about an optimal shift rotation pattern in reducing the health risks of shift health workers while increasing the effectiveness of the treatment of coronavirus (COVID-19) cases. In general, today’s pattern of shift work for health workers is schemed in the eight-day cycle, in which employees work two days in the morning service for seven hours, two days in the evening service for seven hours, and another two days in the night service for ten hours, then followed by two days off. This pattern has the potential to cause burnout and decrease reaction time. The article identifies a new work shift pattern that can accommodate the risk of burnout while simultaneously assisting in the emergency of the corona outbreak. It emphasises the Morning-Evening-Night-Holiday work pattern as an innovative work model that should replace the old work pattern. There are seven advantages of the new work pattern: biological balance, availability of transportation, rapid recovery, reduced risk of COVID-19 transmission, increased patient satisfaction, increased self-control, and improved performance.